Production costs, prices and income of firms - Villalobos Céspedes, Daniel (2015)
The present theoretical research analyzes microeconomic theory in regards to cost of production, prices, and firm’s revenue. We use simple mathematical tools to develop relationships of implied variables in the propounded model. The object of this is to explain microeconomic themes approximately to experiences of firms that produce a single good or service. It concludes that marginal cost and marginal revenue are not the most important factors in defining a firm’s equilibrium, but they are derived from the average cost and average revenue respectively. When consumer demand intensity and average profit rate are taken into consideration, the average cost and average revenue become fundamental concepts of theory cost and competition.